101 facts about ferrets - Horton-Bussey, Claire (Milwaukee, WI : Gareth Stevens Pub., 2002)
Provides information about ferrets, how to care for them, and how to understand their behavior.
Includes bibliographical references (p. 31) and index.
Keywords: Ferrets as pets -- Miscellanea -- Juvenile literature; Ferrets as pets; Pets